Effect of Lambda-cyhalothrin + Carbofuran Application and Habitat Modification on Population Dynamics Of 0rseolia oryzivora (Diptera: Cecidomyiidae) in Relation to its Parasitoids On Rice - Gaba, ibrahim (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
ABSTRACT This experiment was carried out between 2018 and 2019 at the experimental site of National Cereals Research Institute’s identified hot spot (Edozhigi) for Africa rice gall midge (0rseolia oryzivora) infestation in Nigeria. Edozhigi in Niger State is within the southern Guinea savanna agro-ecological zone at latitude 09°45' N, longitude 06°07' E, to test integrated inluence of habitat manipulation, lambda-cyhalothrin and carbofuran on population dynamics of 0. oryzivora in relation to its parasitoids on rice. The treatments were arranged in split-plot and laid out in a RCBD with three replicates. Data were collected on number of tiller / stand, plant height, days to 50 percent flowering, percent incidence, percent severity, percentage parasitism of 0. oryzivora, panicle per meter square, grains per panicle and yield of rice. Data collected were subjected to Analysis of Variance and significant means were separated using Student Newman Keuls Test, (SNK) at 5 % probability. The result showed that Rice plots treated with P. scrubiculatum + 0.38L/ha lambda-cyhalotrin +3.75kg/ha carbofuran had lower incidence (2.36) and severity (1.54) of 0. oryzivora compared with incidence (7.99) and severity (7.40) respectively found in untreated plots (control). It also had significantly higher yield (3263.95kg/ha) compared with the yield (2688.28kg/ha) in control plots. In conclusion, having P. scrobiculatum at boarder of net plots enhanced number of parasitoids and reduced attack of rice by 0. oryzivora. Integration of habitat modification with insecticide application offers better protection of rice against O. oryzivora. Key words: Habitat P. scrobiculatum, Infestation, Modification, Galls.